2021
DOI: 10.1016/j.onehlt.2021.100277
|View full text |Cite
|
Sign up to set email alerts
|

Comparable seasonal pattern for COVID-19 and flu-like illnesses

Abstract: Background During the first wave of COVID-19 it was hypothesized that COVID-19 is subject to multi-wave seasonality, similar to Influenza-Like Illnesses since time immemorial. One year into the pandemic, we aimed to test the seasonality hypothesis for COVID-19. Methods We calculated the average annual time-series for Influenza-Like Illnesses based on incidence data from 2016 till 2019 in the Netherlands, and compared these with two COVID-19 time-series during 2020/2021 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Other studies confirmed the seasonal trend of COVID-19 mortality, but none of them focused on temperate climate countries only. Some of them analyzed individual countries or cities ( Zoran et al, 2021 ; Hoogeveen and Hoogeveen, 2021 ; Choi et al, 2021 ; Danon et al, 2021 ), while others arbitrarily selected sets of states around the world with significant climate differences ( Smith et al, 2021 ; Rouen et al, 2020 ). In addition, most papers focused on incidence rates, which may be biased by the testing capacity of individual countries ( Zoran et al, 2021 ; Hoogeveen and Hoogeveen, 2021 ; Choi et al, 2021 ; Danon et al, 2021 ; Smith et al, 2021 ; Rouen et al, 2020 ; Lagacé-Wiens et al, 2021 ; Christophi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies confirmed the seasonal trend of COVID-19 mortality, but none of them focused on temperate climate countries only. Some of them analyzed individual countries or cities ( Zoran et al, 2021 ; Hoogeveen and Hoogeveen, 2021 ; Choi et al, 2021 ; Danon et al, 2021 ), while others arbitrarily selected sets of states around the world with significant climate differences ( Smith et al, 2021 ; Rouen et al, 2020 ). In addition, most papers focused on incidence rates, which may be biased by the testing capacity of individual countries ( Zoran et al, 2021 ; Hoogeveen and Hoogeveen, 2021 ; Choi et al, 2021 ; Danon et al, 2021 ; Smith et al, 2021 ; Rouen et al, 2020 ; Lagacé-Wiens et al, 2021 ; Christophi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We notice again a slight scattering in the results, which can be ascribed to the test conditions. These outcomes are of paramount importance for the development of air and surface disinfecting devices, but do not explain the particular seasonal epidemiology of SARS-CoV-2 infection, which has been extensively investigated in different regions and countries during this year, suggesting a correlation with [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] some key environmental factors. Concerning the UV light, the idea that viral epidemiology could be modulated by the intensity of the solar pump is rebutted by the observation that the UV-C light emitted by the Sun, the most important UV light source, is filtered and blocked by the ozone layer in the stratosphere.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 appears to be subject to multi-wave seasonality [1,2], comparable to other respiratory viral infections and pandemics since time immemorial [3,4]. It is observed that the COVID-19 community outbreaks have a pattern that is similar to those of other seasonal respiratory viruses [5,6,7,8], whereby the seasonal dips coincide with allergy season in regions in the temperate climate zone [9,10,11]. The same factors that drive the seasonality of flu-like illnesses, appear to drive COVID-19 seasonality: solar radiation including ultraviolet (UV) light, temperature, relative or specific humidity, seasonal allergens (pollens) and allergies, and behavior.…”
Section: Introductionmentioning
confidence: 89%
“…For all datasets we have selected the same overlapping period of COVID-19 and the first full allergy season [ 8], during 2020. The overlapping period runs therefore from February 17, 2020 till September 21, 2020 (n = 218 days), when the total pollen concentrations structurally drop below 10 grains/m 3 as an indication for the end of pollen season.…”
Section: Pagementioning
confidence: 99%